Circular Economy Business Models and Region’s Role in their Implementation - Pavlikha, Nataliia; Antoniuk, Nataliia; Korneliuk, Olga (Publishing House MEERI PAS, 2024)
The theoretical and practical aspects of circular business models are studied. The need to transition from a linear to a CE in order to reduce the “ecological footprint” is substantiated. The importance of the main elements of the CE was analyzed: closed cycles, renewable energy, systems thinking. The international strategic documents on the development of the CE were studied. The key points and areas of implementation, which are defined in the Circular Economy Action Plan, have been studied. They are: make sustainable products the norm in the EU; expand the opportunities of consumers and state buyers; pay special attention to such industries as electronics, batteries and vehicles, packaging, plastics, textiles, construction, food products; reduce waste; make cyclicality work for people, regions and cities. The essence of the concept and elements of the business model are characterized: costs for product creation and development, sales organization costs and the way to make a profit. The main types of business models are highlighted: promotional, affiliate marketing, commission pay, trade, crowdsourcing, manufacturer, franchising, “low-touch”, «razor and blades» and marketplace. According to interaction between business, private individuals and the state, there are such business models: business to business, business to consumer, business to government, consumer to business, consumer to consumer, consumer to government, government to business, government to consumer, government to government. The peculiarities of circular business models and their types are characterized: circular supply models, resource recovery models, product life extension models, sharing models, product service system models. On the basis of foreign experience, the peculiarities of the practical application of business models in various spheres and industries are analyzed; their advantages for the producer and the consumer are investigated. The problems of financial support for the development of the CE have been studied. The necessity of strengthening the participation of regions in the development of the CE is justified; the main areas of activity of the region in this field are outlined.
Keywords: circular economy; linear economy; business model; resource efficiency; sustainable development of the region